Unsymmetrical boron diketonates containing strong electron-donating groups as mechanochromic fluorescent solids. (December 2022) - Mehiaoui, Nawel; Leleu, Stéphane; Kibou, Zahira; Choukchou-Braham, Noureddine; Franck, Xavier; Gallavardin, Thibault
Abstract: New π-conjugated unsymmetrical β-diketones were synthesized thanks to a modular synthetic approach involving in situ generated acylketenes through thermal degradation of 1, 4-dioxin-2-ones. This method gave access to a family of new chromophores featuring either an indoline or a benzothiazole as electron-donating groups in one side and various aromatic moieties in the other side. After complexation with boron difluoride, BDK (Boron DiKetonates) compounds were obtained featuring fluorescence in non-polar solvents. These compounds were also found to be fluorescent in solid state with quantum yield up to 0.22, and their emission wavelength was very sensitive to their crystallinity. Two of these compounds were successfully recrystallized to provide small single crystals and emission spectra were recorded in crystal phase and ground state which showed mechanochromism with a spectral shift of 37 nm. Highlights: A method based on the thermal degradation of 1, 3-dioxin-4-ones was developed to synthesize unsymmetrical β-diketones. Corresponding boron diketonates (BDK) were fluorescent in non-polar solvents, featuring a cyanine optical behavior. In solid state, most of these compounds were fluorescent with quantum up to 0.22, with emission ranging from 575 to 650 nm. Mecanochromism was evidenced in two recrystallized compounds.